SISTEM INFORMASI ADMINISTRASI MAKAM BERBASIS WEBSITE PADA UPTD PEMAKAMAN DINAS PERUMAHAN RAKYAT DAN KAWASAN PERMUKIMAN KOTA JAMBI: Levies, PHP, HTML, MySQL - Surya, Junaidi; Apriyanti, Nila (LP2M Universitas Nurdin Hamzah, 2021)
One of the government institutions that requires a funeral information system is the UPTD Cemetery of the Jambi City Public Housing and Settlement Areas which is the only UPTD in Jambi City that is engaged in funerals. In the case of the data collection system for registration of corpses and levies, manual recording is still carried out using files, thus it takes time because officers have to look for data on vacant burial grounds first, and also make it difficult for officers to search for existing funeral data if they needed back. In terms of data archiving, it is still done manually on the shelves which sometimes the condition of the file is damaged. The data in question is data on corpses, heirs and levies. Due to the existence of levies here, in terms of recording, sometimes the amount of retribution results is inaccurate.